Estimating the incidence of actionable drug-gene interactions in Japanese patients with major depressive disorder - Hatano, Masakazu; Ikeda, Masashi; Saito, Takeo; Miyata, Masami; Iwata, Nakao; Yamada, Shigeki (Frontiers in Psychiatry, 2025)
BackgroundAlthough several guidelines provide dosing recommendations for antidepressants based on patients’ genetic information, pharmacogenetic testing for antidepressant use is rarely routinely performed in Japan. To clarify the clinical impact of pharmacogenetic testing, this study estimated the potential drug-gene interactions for first-time antidepressant treatment in Japanese patients with major depressive disorder.MethodsThis study retrospectively included Japanese patients who were registered for depressive episodes (F32, International Classification of Diseases, Tenth Revision) and initiated on antidepressants between July 2022 and March 2023. Antidepressant prescription rates were calculated using a nationwide hospital-based database (Medical Data Vision Co., Ltd). The incidence of actionable drug-gene interactions was estimated by multiplying the first-time prescription rate of each relevant antidepressant by the frequency of its corresponding actionable phenotype.ResultsA total of 3,197 patients were included in the analysis. Escitalopram was the most frequently prescribed antidepressant (18.7%, n = 597), followed by mirtazapine (17.5%, n = 561), and sertraline (15.4%, n = 493). Of the patients receiving their first treatment of major depressive disorder, 56.5% (n = 1,807) were prescribed a drug with actionable pharmacogenetic implications, and 26.4% (n = 844) were estimated to have required actionable therapeutic recommendations. The highest incidence of actionable drug-gene interactions was observed in escitalopram and CYP2C19 pairs (12.4%, n = 398). For sertraline and CYP2C19 or CYP2B6 pairs, the incidence was 11.0% (n = 352). Among all antidepressants, paroxetine had the highest incidence of actionable drug-gene interactions related to CYP2D6 at 1.8% (n = 56); this interaction was rarely observed with other antidepressants (<1%).ConclusionsWe estimated that one in four Japanese patients with major depressive disorder who were prescribed first-time antidepressants had actionable drug-gene interactions. These results suggest that pre-emptive pharmacogenetic testing in the treatment of major depressive disorder could have important clinical implications.